2014
DOI: 10.1002/jbmr.2291
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Incident Hip Fracture with the Estimated Femoral Strength by Finite Element Analysis of DXA Scans in the Study of Osteoporotic Fractures

Abstract: A bone fractures only when loaded beyond its strength. The purpose of this study was to determine the association of femoral strength, as estimated by finite element (FE) analysis of DXA scans, with incident hip fracture in comparison to hip BMD, FRAX® and hip structure analysis (HSA) variables. This prospective case-cohort study included a random sample of 1941 women and 668 incident hip fracture cases (295 in the random sample) during a mean±SD follow-up of 12.8±5.7 yrs from the Study of Osteoporotic Fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 63 publications
1
36
0
2
Order By: Relevance
“…assuming the plane-stress approach, i.e., considering that proximal femur is a plate with a constant thickness [65,66]. Then, isotropic inhomogeneous material properties were derived from vBMD using the empirical equations of Morgan and colleagues [67,68] …”
Section: Calculation Of Impact Force and Hip Fracture Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…assuming the plane-stress approach, i.e., considering that proximal femur is a plate with a constant thickness [65,66]. Then, isotropic inhomogeneous material properties were derived from vBMD using the empirical equations of Morgan and colleagues [67,68] …”
Section: Calculation Of Impact Force and Hip Fracture Riskmentioning
confidence: 99%
“…If FRI is greater than one, the patient is in a high risk of hip fracture. The femoral strength was then derived as the onset impact force that causes the FRI exceeding one [65,66]. This was calculated by scaling the impact force by the factor FRI as:…”
Section: Calculation Of Impact Force and Hip Fracture Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have demonstrated that QCTbased FEA significantly improves the prediction of bone strength than densitometric measures [225,229]. Reported clinical studies has shown FEA estimated bone strength is indeed an independent fracture risk predictor [230,231]. However, the incremental contribution made by FEA over BMD in discriminating fracture cases is still marginal and the role of FEA in routine clinical examination of fracture risk has not been established.…”
Section: Links Between Biomechanical Variables and Clinical Risk Factorsmentioning
confidence: 98%
“…FEA itself has no ability to predict the risk of fall and the types of fall. In finite element modeling of hip fractures, sideways fall from standing height or single-leg stance loading conditions are mostly used [8,230,231]. However, real-world accident falls are much more complicated.…”
Section: Links Between Biomechanical Variables and Clinical Risk Factorsmentioning
confidence: 99%